ANALISIS METODE ARBA’IN PADA KEMAHIRAN QIROATUL KUTUB SANTRIWATI PONDOK PESANTREN ISLAM AL MUKMIN SUKOHARJO - Rizki Azizah; Muh. Fajar Shodiq (El-Tsaqafah : Jurnal Jurusan PBA, 2024)
This article aims to measure the ability of nahwu and shorof as the main capital in the proficiency of Qiroatul Kutub, knowing the inhibiting and supporting factors for the ability of santriwati in Qiroatul Kutub, and knowing what methods are applied in learning Qiroatul Kutub proficiency. The research method used is descriptive qualitative research. By using three pedagogical, sociological, and psychological approaches. Data collection techniques were carried out by observation, interviews, and tests. The results showed that the ability of nahwu and shorof of female students majoring in religion was in the good category and showed indications of progress after the roll-out of Qirotaul Kutub learning with the Arbai'in method.  Factors affecting the ability of Qirotaul Kutub students majoring in religion are the minimum duration of learning time for teachers and students, the different intelligence abilities of santriwati in interest in learning and differences in basic Nahwu Shorof abilities, the adjustment of the qirotaul kutub curriculum which has undergone revision is one of the inhibiting factors from the instrumental side of the institution.   The Qiroatul Kutub method used is the Arbai'in Demak method authored by Al Mukarrom kyai Muharror Khudori, this method prioritizes efficiency and innovation in reading bare books or Arabic texts with the help of the Arbai'in Demak method. This method frequently prioritises efficiency and innovation in reading bare books or Arabic texts with the aim that educators or teachers and all students are able to master proficiency in Qiroatul Kutub.